Analysing B2B electronic procurement benefits –information systems perspective - Piotrowicz, W; Irani, Z (2009)
This paper presents electronic procurement benefits identified in four case companies. The benefits achieved in the case companies were classified according to taxonomies from the Information Systems discipline. Existing taxonomies were combined into a new taxonomy which allows evaluation of the complex e-procurement impact. Traditional financial-based methods failed to capture the nature of e-procurement benefits. In the new taxonomy, e-procurement benefits are classified using scorecard dimensions (strategic, tactical and operational), which allows the identification of areas of e-procurement impact, in addition the benefits characteristic is captured (tangible, intangible, financial and non-financial).